A long-acting interleukin-7, rhIL-7-hyFc, enhances CAR T cell expansion, persistence, and anti-tumor activity - Miriam Y. Kim; Reyka Jayasinghe; Jessica M. Devenport; Julie K. Ritchey; Michael P. Rettig; Julie O’Neal; Karl W. Staser; Krista M. Kennerly; Alun J. Carter; Feng Gao; Byung Ha Lee; Matthew L. Cooper; et al. (Nature Communications, 2022)
Chimeric antigen receptor T cells represent a breakthrough treatment in hematologic malignancies, but insufficient level of cytotoxicity and persistence of T cells might compromise success. Authors show here that a recombinant long acting form of interleukin-7 enhances proliferation, persistence and cytotoxicity of the engineered T cells, resulting in long term disease remission.